Competency Development Strategies to Enhance Personnel Performance Efficiency Mahamakut Buddhist University: Competency Development Strategies to Enhance Personnel Performance Efficiency Mahamakut Buddhist University - Ueakit, Amorn; Phrametheewatcharaphorn; Lawalee, Banjong; Jumrearnsan, Wongchanok; Chomcharee, Chatchai (RATANABUTH JOURNAL, 2024)
The objectives of this research were 1) to study the components and indicators of competency development strategies to enhance personnel performance efficiency Mahamakut Buddhist University. 2) To examine the structural validity and structural reliability of the components and indicators for to development strategies to enhance personnel performance efficiency Mahamakut Buddhist University, and 3) to create a strategic model of competency development to enhance the performance of personnel of Mahamakut Buddhist University. The sample in this research consists of personnel from Mahamakut Buddhist University, totaling 165 individuals. The research instrument used is a questionnaire, and the statistical methods for data analysis include mean, standard deviation, and confirmatory factor analysis. The research results were as follows:1) the components and indicators of the study of components and indicators of competency development to enhance the work performance of personnel of Mahamakut Buddhist University consisted of 5 components: social responsibility, working smart, unity, creativity, and morals. 2) The results of the assessment of the structural validity and reliability of the components and indicators for developing competencies to enhance the performance efficiency of personnel at Mahamakut Buddhist University indicate that all 5 components and 20 indicators are statistically significant at the 0.05 level. The model has a structural reliability of 0.924, which is greater than 0.60, indicating that the model is consistent and suitable for the empirical data. 3) Strategic model of competency development to enhance efficiency of personnel work of Mahamakut Buddhist University using systems theory as follows: 1) Input factors, comprising the current status of personnel work of Mahamakut Buddhist University, 2) Process, using competency development according to PIE framework, namely: (1) Performance (2) Improvement (Development) (3) Enhancement (Enhancement) by integrating the principle of Iddhipada 4, which means the path to success, which has 4 important components, namely: (1) Chanta (2) Viriya (3) Chitta (4) Wimams. Output factors is the strategic model of competency development to enhance efficiency of personnel work of Mahamakut Buddhist University.